Research on the Fixation Strength of High-Temperature Geothermal Drilling Cone Bit Teeth - Yang, Yan; Song, Dongdong; Chen, Lian; Yang, Yingxin; Ren, Haitao; Qiu, Shunzuo; Huang, Zequan (Energies (Basel), 2025)
During the drilling process of high-temperature geothermal wells, the high temperature at the bottom of the well and the complex lithology of the formation lead to poor tooth loss prevention in cone drill bits. This issue seriously affects the life and efficiency of geothermal drilling. The stability of the wellbore is one of the key issues in the drilling process of high-temperature geothermal wells, and the fixed-tooth strength of the roller drill bit directly affects the stability of the wellbore and drilling efficiency. The heat transfer effect of the wellbore will exacerbate the thermal expansion and performance degradation of the drill bit material in high-temperature environments, leading to a decrease in the strength of the fixed teeth. To address this, this study used a high-temperature experimental apparatus to systematically test the fixed-tooth strength of roller drill bits. By using five types of tooth spacing: 4, 6, 8, 10, and 12 mm, three types of tooth diameters: 12, 14, and 16 mm, and three types of interference fit: 0.075, 0.095, and 0.115 mm, the maximum fastening force of fixed teeth was measured under different conditions, and its variation pattern was analyzed. The experimental results show that the higher the temperature, the weaker the tooth-fixing strength. Under the same perforation distance, the maximum fastening force decreases with increasing temperature. Compared with normal temperature, the maximum fastening force decreases by about 49.6–64.5%. At the same temperature, the maximum fastening force is the largest when the perforation distance is 10 mm. When the temperature increases, the maximum fastening force increases with the tooth diameter; that is, the larger the tooth diameter, the better the tooth-fixing effect. At the same temperature, the maximum fastening force first increases and then decreases with increasing interference. The maximum fastening force is the largest when the interference is 0.095 mm. At 120 °C, 180 °C, and 240 °C, the maximum fastening force is reduced by 21.9%, 29.4%, and 56.6%, respectively, compared to normal temperature. The study reveals the variation law of tooth-fixing strength under high-temperature conditions and proposes tooth-fixing methods and suggestions suitable for high-temperature geothermal wells. This provides a scientific basis for solving the problem of tooth loss of roller bits in high-temperature geothermal drilling and has important theoretical and practical application value.